2009
DOI: 10.1002/ab.20313
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and change in social and physical aggression from middle childhood through early adolescence

Abstract: For a sample followed from age 9–13 (N=281), this investigation examined developmental trajectories for social and physical aggression as measured by teacher ratings. Trajectories for both forms of aggression were estimated first separately, then jointly. Mean levels of both social and physical aggression decreased over time for the overall sample, but with high variability of individual trajectories. Subgroups followed high trajectories for both social and physical aggression. Joint estimation yielded six tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
98
5
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(119 citation statements)
references
References 66 publications
(135 reference statements)
8
98
5
8
Order By: Relevance
“…The transient association of early puberty with physical aggression may be explained by generally low and decreasing levels of physical aggression in adolescent girls. 27 Consistent with some previous research, 28 early puberty was not related to relational and nonphysical aggression.…”
Section: Discussionsupporting
confidence: 87%
“…The transient association of early puberty with physical aggression may be explained by generally low and decreasing levels of physical aggression in adolescent girls. 27 Consistent with some previous research, 28 early puberty was not related to relational and nonphysical aggression.…”
Section: Discussionsupporting
confidence: 87%
“…The use of indirect aggression also increases with age [22,[38][39][40] and is used at a similar rate [41] by females during adolescence [22] and young adulthood [33]. The fact that indirect aggression is primarily used by teenage girls and young women, who direct their aggression at same-sex peers, is in keeping with the hypothesis that indirect aggression is used in the context of competing for mates.…”
Section: Introductionmentioning
confidence: 89%
“…3,18 With regard to their reactions to aggressive behavior, boys and girls may use different strategies. 19 Recent studies have suggested that searching for support, avoiding the aggressor, and retaliation are strategies commonly used by children when they are victims of aggression from their peers.…”
mentioning
confidence: 99%